Fermentasi Tradisional, Khasiat Modern: Tapai Ketan Hitam sebagai Solusi Nutraceutical Penurun Kolesterol - Fathiya Rizki Aninda; Ardi Mustakim (International Forum of Researchers and Lecturers, 2025)
Black sticky rice tapai is a traditional Indonesian fermented food that has long been consumed by the public for its distinctive taste and high cultural value. However, with the increasing demand for functional foods and natural-based products that can support health, attention for black sticky rice tapai has shifted from being simply a traditional food to an object of scientific study in the nutraceutical field. Black sticky rice, the basic ingredient for tapai, contains important bioactive compounds such as anthocyanins, flavonoids, B-complex vitamins, and soluble fiber, which have been shown to play a role in lowering cholesterol levels, inhibiting LDL cholesterol oxidation, and increasing HDL cholesterol levels in the blood. The fermentation process further enhances the biological activity of these compounds, making black sticky rice tapai have a higher therapeutic value than ordinary black sticky rice. The purpose of this study was to examine the potential of black sticky rice tapai as a natural, tradition-based solution for lowering cholesterol levels, while also supporting the development of local foods into modern health products that are safe, effective, and affordable. The study was conducted using a descriptive literature review method of various scientific articles, textbooks, and relevant research results that discuss the nutritional content of black sticky rice, the benefits of fermentation, and the effect of active components on lipid metabolism. The study results show that regular consumption of black glutinous rice tapai has the potential to lower total and LDL cholesterol levels and increase HDL through a combination of antioxidant effects, cholesterol binding by fiber, and increased fat excretion. In addition, the potential of black glutinous rice tapai as a nutraceutical is also relevant in supporting the preservation of local-based culture and food independence.